PENGARUH PENGGUNAAN GADGET TERHADAP MANAJEMEN WAKTU BELAJAR PADA PESERTA DIDIK DI SMP NEGERI 3 ENTIKONG - Susilawati; Halida; Elli Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of gadget use, the level of learning time management, and the effect of gadget use on the learning time management of eighth-grade students at SMP Negeri 3 Entikong. This study employed a quantitative approach with a correlational research design. The population of this study consisted of 98 students. Data collection was carried out through indirect communication using a 4-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive and inferential analysis with the assistance of SPSS version 22 and 23. The results of the study showed that there was a significant effect of gadget use on students’ learning time management, with a significance value of 0.000 (p < 0.05). The magnitude of the effect of gadget use on learning time management was indicated by the coefficient of determination value of 0.644, which means that gadget use contributed 64.4%, while the remaining 35.6% was influenced by other factors outside the scope of this study. Based on these findings, it can be concluded that gadget use has an effect on students’ learning time management. Therefore, proper supervision and guidance are needed so that gadget use can support the learning process optimally.